MUCET 2012 - Noor Syahidah, Sabran (Penerbit UMP, 2012)
Malaysian Technical Universities Conference on Engineering & Technology (MUCET 201 2) was held from November 20-21, 2012, at Seri Malaysia Hotel, Kangar, Perlis.